CARDIOVASCULAR RISK FACTORS, NON-HDL CHOLESTEROL, AND OVERWEIGHT AMONG ADOLESCENTS: CLINICAL AND SOCIODEMOGRAPHIC ASPECTS - Mota Mourão Schreiber, Daniella; Mota Mourão Alvarenga, Tassiana; Soares Zuquim, Rilder; Luiz Gomes Carneiro, André; Magela Durães, Geraldo; Roberto de Matos e Ávila, Waldney; Fellipe Sousa Jacome, Kaio; Gonçalves da Silva, Rodrigo; Donato Bauman, Claudiana; Mesquita Antunes, Felipe; Américo Pires Pinto, Mauro; Teixeira de Freitas , Getúlio (Revista Gênero e Interdisciplinaridade, 2026)
The objective of this study was to estimate the prevalence ratio of increased non-HDL cholesterol with cardiovascular risk factors in a representative sample of adolescents from public schools. This is a descriptive and cross-sectional study, carried out with adolescents aged between 10 and 16 years from public schools in Montes Claros, northern Minas Gerais, Brazil. The proportion of adolescents classified as overweight (31.4%) did not differ significantly between genders and was significantly higher among younger adolescents (47.6%) compared to all other age groups. The prevalence of central obesity was also higher in adolescents aged 10-11 years, as well as metabolic syndrome and hypertriglyceridemia, but without significant difference. The adjusted prevalence ratio for LDLc was 1.71 (95% CI 1.68-1.73; p < 0.00), indicating that an increase in each unit of non-HDL cholesterol increases the probability of high LDLc by 71%. It was also evidenced that adolescents with high non-HDL cholesterol have a prevalence of 1.14 times more hypertriglyceridemia, adjusted for gender and age group. The prevalence of non-HDL cholesterol was high among adolescents, as well as cardiovascular risk factors, in this sense, effective school programs for health promotion and regular physical activity are needed.